Jailed Individuals’ Perceptions of Procedural Justice and Suicidal Ideation: An Empirical Examination - Abderhalden, Frances P. (Crime & delinquency, 2024)
Suicide ideation (SI) represent a major public health concern, especially within incarcerated settings. Although prior research acknowledges the influence of individual characteristics, less research has examined how perceptions of procedural justice relate to individuals? maladaptive behavior while incarcerated. Recently, scholarship has included self-injurious thoughts and behaviors as an outcome of perceived procedural justice for incarcerated individuals. This study expands on prior work, by exploring perceptions of procedural justice related to SI using a jail sample from the United States (n?=?397). We found strong support that higher perceptions of procedural justice are related to reduced frequency of suicidal ideation in jail. We discuss these implications in relation to the critical impact on public health and safety of this vulnerable population.